Jawetz, Melnick, & Adelberg's medical microbiology - 23rd; Ed (Lange medical book., 2004)
This comprehensive and authoritative text covers the basic and clinical aspects of microbiology. Focusing on the microbiology concepts that are essential to the diagnosis of clinical infections, it features review questions in USMLE format at the end of each chapter as well as a clinical correlations chapter that offers case studies focusing on the differential diagnosis and management of microbial infections.